2023
DOI: 10.3389/fpls.2023.1192356
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing genome-wide genetic diversity, population structure and linkage disequilibrium in Ethiopian durum wheat gene pool

Abstract: Yanyang Liu, Henan Academy of Agricultural Sciences (HNAAS), China; Landraces are an important genetic source for transferring valuable novel genes and alleles required to enhance genetic variation. Therefore, information on the gene pool’s genetic diversity and population structure is essential for the conservation and sustainable use of durum wheat genetic resources. Hence, the aim of this study was to assess genetic diversity, population structure, and linkage disequilibrium, as well as to identify regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Egyptian clover cultivars are not pure lines because of their allogamy, to avoid inbreeding depression. As reported in many previous studies (Moeller et al, 2007;Mulugeta et al, 2023), cultivar-specific characteristics can be identified using the population genomic analysis to examine genetic variations within and between cultivars. In this study, we evaluated the genetic diversity level within Helaly.…”
Section: Discussionmentioning
confidence: 99%
“…Egyptian clover cultivars are not pure lines because of their allogamy, to avoid inbreeding depression. As reported in many previous studies (Moeller et al, 2007;Mulugeta et al, 2023), cultivar-specific characteristics can be identified using the population genomic analysis to examine genetic variations within and between cultivars. In this study, we evaluated the genetic diversity level within Helaly.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with common wheat, durum wheat has only genomes A and B. It is easier to cross with wild relatives to develop germplasms containing alien chromosomes in their genetic backgrounds ( Mulugeta et al., 2023 ). To date, haploid plants in durum wheat have mainly been induced by microspore culture and intergeneric crossing between tetraploid wheat and maize ( Cistué et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%